Peran Serta Masyarakat Dan Model Pengelolaan Sampah Di Kecamatan Kaur Selatan Kabupaten Kaur - Suryanto, Suryanto; Barchia, M. Faiz; Brata, Bieng; Santoso, Urip; Yurike, Yurike (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
This research aims to analyze community participation in waste management in the form of willingness to pay and find out the management model in South Kaur District. The types of data used in research are primary data and secondary data. The research location was carried out in nineteen villages in South Kaur District, the research time was 30 days for distributing questionnaires, and the respondents obtained were 100 respondents spread across nineteen villages. Based on the research results, it was found that the WTP contribution (willingness to pay) in waste management in South Kaur District was IDR. 5,875. Simultaneous test results show that the independent variables, namely age, gender, education level, number of family members and income have an effect on WTP (people's willingness to pay) and based on the statistical F test results show that the income variable has a significant effect on WTP (willingness to pay). Based on the questionnaire and Indonesian National Standards (SNI) regarding waste management in South Kaur District, it can be concluded into 2 (two) namely the household scale waste management model and the communal scale waste management model. People's habit of disposing of rubbish is by burning it themselves, the rubbish still sometimes has to be sorted, and there are still people who don't have rubbish boxes, so local governments are expected to carry out regular outreach, provide and add facilities and infrastructure for rubbish disposal sites to make it easier for the public to dispose of rubbish. waste, as well as revising and making regional regulations regarding levies and waste management standards. There is a need for cooperation from all parties, both government and society, to always maintain cleanliness and reduce waste through 3R waste management (Reduce, Reuce, Recycle). Keywords: Community Role, Waste Management Model, Willingness To Pay